Pengujian Fungsionalitas Sistem Pengamanan Digital Watermarking Kartu Indonesia Sehat Menggunakan Algoritma MSB - Cahyani, Ni Putu Intan; Santi Astawa, I Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 3 (2023): JNATIA Vol. 1, No. 3, Mei 2023, 2023)
The rapid development of technology makes the dissemination of information also develop, and the use of digital data is increasingly used even in the health sector, one of which is when registering at health institutions online so that when registering it is necessary to scan the Healthy Indonesia Card to register. Sometimes there are onkuns who are not responsible for misusing it to do evil things, so based on these problems, the Healthy Indonesia Card (KIS)  that will be used should be inserted with a watermark to minimize unwanted events. Watermark is a method of inserting information into digital data that aims to protect data ownership. One technique that can be used is the steganography technique, which uses the MSB (Most Significant Bit) algorithm. The length of time it takes to insert a watermark on a Healthy Indonesia Card (KIS) depends on how much text will be inserted to become a watermark